A technology assessment on the capabilities of ABS-CBN corporation and information technology division toward digital convergence - Abarra, Geraldine De Leon
ABS-CBN Corporation (ABS-CBN) is the largest integrated media and entertainment company in the Philippines. The organization is transitioning from broadcast media to multi-media. The Information Technology Division plays an important role in this digital convergence. This paper studies the trends toward digital convergence and analyzes the barriers that ABS-CBN Corporation and IT Division should overcome to meet the strategic objective of achieving digital convergence. This paper concludes with recommendations and scenarios toward digital synergy.